DIAGNOSE OF THYPOID FEVER WITH WIDAL TEST - Nurya Wardana, I Made Tomik; Herawati, Sianny; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana, 2014)
Thypoid fever is one of infection systemic disease cause by Salmonella enterica serotype typhi, this bacterium is member of family Enterobacteriaciae. Everyone with thypoid fever bring the bacterium in blood stream and gastrointestinal sytem so that it can transmit the infection to others directly through water or food that has been contaminated. Laboratory examination to establish a diagnosis of typhoid fever is with conventional methods, namely the culture of the bacterium and serological test Widal and non-conventional method, namely Polimerase Chain Reaction (PCR), Enzyme Immunoassay Dot (EID) and Enzyme-Linked Immunosorbent Assay (ELISA). The definitive diagnosis of typhoid fever is with isolation of Salmonella enterica serotype typhi from blood, urine or other body fluids. It is often not possible in developing countries because of inadequate bakteriologik facilities on many small hospitals, while typhoid fever is an endemic disease in the country. With this kind of situation, the diagnosis should be enforced by connecting the corresponding clinical symptoms with typhoid fever and the presence of antibody titer is increasing significantly in the blood against antigens O or H antigens of Salmonella enterica serotype typhi (Widal test).
Keywords: Thypoid fever, Widal test